Baseline 2004: Changing the way we manage water for food, livelihoods, health and the environment - Harrington, Larry W.; Gichuki, Francis N.; Gaheb, K.; Woolley, Jonathan N. (CGIAR Challenge Program on Water and Food, 2006)
There are many options for enhancing food production from fish in managed aquatic systems.The most appropriate technology, however, will vary from place to place, and the conditions under which one technology is prefered over another are still not well defined.